Search for approaches to producing organic fertilizers from raw materials of plant and animal origin. Issue 1 (October 2020) - Valiullin, Lenar; Titova, Valentina; Tremasov, Yurii; Huzin, Damir; Nabatov, Alexey; Validov, Shamil; Bogun, Inna; Cheremisin, Alexey; Kudeyarov, Valery
Abstract: Due to the annual increase in emissions of animal and poultry waste into the environment, scientists around the world are increasingly interested in improving technologies to accelerate the processing of agricultural waste. In the presented work, 6 microorganisms were selected: Lactobacillus spp., thermophilic bacteria (Bac. subtilis), Clostridium spp., Penicililum spp., Saccharomyces cerevisiae, Micrococcus nishomyaensis) to accelerate the processing of animal waste. The toxicity and toxigenicity of newly isolated strains of microorganisms was assessed. At the same time, it was found that the strains of microorganisms do not have toxicity and toxigenicity.